Selective Aerobic Oxidation of HMF to 2, 5‐Diformylfuran on Covalent Triazine Frameworks‐Supported Ru Catalysts. Issue 4 (13th January 2015) - Artz, Jens; Mallmann, Sabrina; Palkovits, Regina
Abstract The selective aerobic oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐diformylfuran has been performed under mild conditions at 80 °C and 20 bar of synthetic air in methyl t‐butyl ether. Ru clusters supported on covalent triazine frameworks (CTFs) allowed excellent selectivity and superior catalytic activity compared to other support materials such as activated carbon, γ‐Al2O3, hydrotalcite, or MgO. CTFs with varying pore size, specific surface area, and N content could be prepared from different monomers. The structural properties of the CTF materials influence the catalytic activity of Ru/CTF significantly in the aerobic oxidation of HMF, which emphasizes the superior activity of mesoporous CTFs. Recycling of the catalysts is challenging, but promising methods to maintain high catalytic activity were developed that facilitate only minor deactivation in five consecutive recycling experiments.